Carbohydrate loading in human muscle: an improved 1 day protocol - Bussau, V. A.; Fairchild, T. J.; Rao, A.; Steele, P.; Fournier, P. A. (European Journal of Applied Physiology, 2002)
It is generally acknowledged that even without a glycogen-depleting period of exercise, trained athletes can store maximal amounts of muscle glycogen if fed a carbohydrate-rich diet for 3 days. What has never been examined is whether under these conditions this many days are necessary for the content of muscle glycogen to attain these high levels. To examine this issue, eight endurance-trained male athletes were asked to eat 10 g·day-1·kg-1 body mass of high-carbohydrate foods having a high glycaemic index over 3 days, while remaining physically inactive. Muscle biopsies were taken prior to carbohydrate loading and after 1 and 3 days of eating the carbohydrate-rich diet. Muscle glycogen content increased significantly (P<0.05) from pre-loading levels of [mean (SE)] 95 (5) to 180 (15) mmol·kg-1 wet mass after only 1 day, and remained stable afterwards despite another 2 days of carbohydrate-rich diet. Densitometric analyses of muscle sections stained with periodic acid-Schiff not only supported these findings, but also indicated that only 1 day of high carbohydrate intake was required for glycogen stores to reach maximal levels in types I, IIa, and IIb muscle fibres. In conclusion, these findings showed that combining physical inactivity with a high intake of carbohydrate enables trained athletes to attain maximal muscle glycogen contents within only 24 h.